Mogway: um arcabouço para bancos de dados múltiplos grafos - Padoa, Carlos Eduardo Fernandes de (2017)
Graphs are a powerful representation technique, capable of capturing the relationship between entities. They are useful to understand a wide variety of data sets from many areas like science, government and business. In the last years has resurged the interest in storing and managing graph data due to the realization that investigating the interconnections between entities may lead to interesting insights in a variety of problems. Most of the available graph tools work with the single graph model, which is not suitable for certain problems. Besides that, there is no consensus on what is the best way to implement a graph database, and no standard query language has been defined to graph databases yet. This thesis describes Mogwai, a framework to allow the creation and utilization of graph databases with multiple graphs, and MogwaiQL, a descriptive query language designed to allow querying the database at a high level of abstraction.